Geographical inequality in service utilization for primary aldosteronism screening: spatial epidemiological study in Southern Thailand - Onnicha Suntornlohanakul; Suporn Sakarin; Noppadol Kietsiriroje; Hutcha Sriplung (BMC, 2022)
Abstract Background Primary aldosteronism (PA), the most common cause of secondary hypertension is considered as a "major public health issue" due to higher risk of cardiovascular complications compared to blood-pressure-match hypertension and increase in prevalence around the world. In Thailand, though PA screening is provided under the universal health coverage, the service can be offered only at some centers. Hence, the service availability affects an accessibility of health care in patients. Our study aimed to evaluate the service utilization in PA screening and diagnosis in terms of geographical inequality in health resources in Southern Thailand. Methods Data of 688 patients who underwent PA screening from 2011 to 2017 were obtained from the electronic database of Songklanagarind Hospital, a super-tertiary center in this region. The patients' residence in the province, district and subdistrict were transformed to a 6-digit numbers corresponding to the global one (GADM©). The areas with PA screening and diagnosis were visualized by disease mapping procedures. A general log linear model was used to identify the factors affecting patient's service accessibility. Results From the geographic distribution, patients living in or near the area of the super-tertiary center (Songkhla) had high probability of receiving PA screening. The analysis of factors contributing to PA screening by multivariate log-linear model demonstrated that the distance from the super-tertiary center was a predictive factor for screening while the presence of endocrinologists and cultural differences were not. The chance of patients living in Songkhla, living less than 200 km, and more than 200 km from Songkhla to receive PA screening was 100, 82, and 66%, respectively. The crude incidence rate of PA in Southern Thailand was 1.66/106 person-years. The provinces located adjacent to the Andaman Sea had the highest incidences of PA (3.62-5.17 patients/106 person-years). Conclusions There is still geographical inequality and the strategy to decrease the barrier should be resolved. The policymaker should develop a transfer system of blood tests for PA investigation from the local hospital to reduce the burden such as transportation costs in patients who live far away from the super-tertiary hospital. In addition, PA screening should be implemented in hypertension care plan.